Cure of human diabetic neuropathy by HPLC validated bark extract of Onosma echioides L. root. Issue 18 (17th September 2019) - Shoaib, Ambreen; Dixit, Rakesh Kumar; Badruddeen; Rahman, Md. Azizur; Bagga, Paramdeep; Kaleem, Sarjeel; Siddiqui, Sahabjada; Arshad, Md.; Siddiqui, Hefazat Hussain
Abstract: HPLC validated hexane bark extract of Onosma echioides L. root (OE) was evaluated for cure of human diabetic neuropathy in human neuroblastoma cell line. HPLC analysis was performed. Human neuroblastoma cells were grouped into control, normal glucose, high glucose (HG) and HG plus different concentrations of OE extract (10, 25 and 50 μg/mL). MTT, DCFH-DA staining and nuclear condensation assays were performed on neuroblastoma cells to evaluate antiproliferative activity, ROS activity level and apoptotic effect of OE. HPLC analysis revealed the existence of maximum yield of shikonin in n -hexane extract of OE. Exposure with different concentrations of OE effectively decreased ROS level and apoptosis of cells and as a result improved the viability of cells in a dose dependent manner in response to HG-induced oxidative stress. Thus, OE possesses the property to cure human diabetic neuropathy and further can be clinically tested for its use in diabetic neuropathy. Abstract :